2017
DOI: 10.7150/ijbs.19666
|View full text |Cite
|
Sign up to set email alerts
|

ATP2B1 gene Silencing Increases Insulin Sensitivity through Facilitating Akt Activation via the Ca2+/calmodulin Signaling Pathway and Ca2+-associated eNOS Activation in Endothelial Cells

Abstract: Endothelial cell insulin resistance may be partially responsible for the higher risk of atherosclerosis and cardiovascular disease in populations with insulin resistance and type 2 diabetes mellitus (T2DM). A genome-wide association study revealed a significant association between the ATPase plasma membrane Ca2+ transporting 1 (ATP2B1) gene and T2DM in two community-based cohorts from the Korea Association Resource Project. However, little is known about the implication of the ATP2B1 gene on T2DM. In the prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 40 publications
2
17
0
1
Order By: Relevance
“…30,31 In addition, eNOS is a Ca 2+ /CaM-dependent enzyme and is responsible for NO generation, which subsequently exhibits anti-oxidative, anti-inflammatory, and vascular regulatory activities. 32 The data presented in this study shows that the CaM levels and NO concentration were significantly decreased in the DC rats (P < 0.05). In agreement with the results of previous studies, long-term STZ-induced diabetes was found to cause a significant decrease in CaM levels in the aortic tissues and disrupted the balance between NO and ROS.…”
Section: Wileyonlinelibrarycom/jsfasupporting
confidence: 49%
See 2 more Smart Citations
“…30,31 In addition, eNOS is a Ca 2+ /CaM-dependent enzyme and is responsible for NO generation, which subsequently exhibits anti-oxidative, anti-inflammatory, and vascular regulatory activities. 32 The data presented in this study shows that the CaM levels and NO concentration were significantly decreased in the DC rats (P < 0.05). In agreement with the results of previous studies, long-term STZ-induced diabetes was found to cause a significant decrease in CaM levels in the aortic tissues and disrupted the balance between NO and ROS.…”
Section: Wileyonlinelibrarycom/jsfasupporting
confidence: 49%
“…In agreement with the results of previous studies, long-term STZ-induced diabetes was found to cause a significant decrease in CaM levels in the aortic tissues and disrupted the balance between NO and ROS. 32 Moreover, Long et al reported that the Ca 2+ /CaM/eNOS signaling pathway could enhance insulin sensitivity. [32][33][34] Xi and coworkers.…”
Section: Wileyonlinelibrarycom/jsfamentioning
confidence: 99%
See 1 more Smart Citation
“…The PI3K/Akt pathway provides essential signaling for cell survival and proliferation. Signaling from different eNOS agonists, such as VEGF, insulin, and estrogen can affect eNOS activity through the PI3K/AKT pathway [47][48][49]. It has been reported that activations of the survival signal PI3K/Akt pathway and the endothelial-specific eNOS/NO pathway were closely associated with vascular remodeling and angiogenesis [50,51].…”
Section: Discussionmentioning
confidence: 99%
“…The plasma membrane calcium pump (PMCA) plays an important role in cellular calcium homeostasis (Ryan et al, 2015). The ATP2B1 gene, in hens located on chromosome 1, region 43 273 706-43 305 815 bp, encodes plasma membrane calcium ATPase 1 (PMCA1) (Horecka et al, 2015;Long et al, 2017, Horecka et al, 2018. Because most of studying proteins are involved in osteogenesis, bone remodelling and process of calcium metabolism, so polymorphisms of genes, encoding selected proteins, may play an important role in the pathogenesis of osteoporosis, by influencing protein formation and consequently bone formation.…”
Section: Introductionmentioning
confidence: 99%